Midimew-connected Gaussian network - Antari, Nuha Hussain; Rahman, M.M. Hafizur; Mohd. Nor, Rizal; Tengku Sembok, Tengku Mohd (The Institute of Electrical and Electronics Engineers, Inc., 2016)
Midimew-Connected Gaussian Network (MGN) is a hierarchical interconnection network which is able to interconnect millions of nodes in the network to achieve high performance and cost-effective design for massively parallel computing system (MPC). MGN consists of multiple basic modules with Wraparound links (MIDIMEW) to form the higher level network, where the basic module of MGN is dense Gaussian network with additional links in its edge nodes. This paper focuses on the architecture design of MGN, and computes the performance parameters such as degree, arc connectivity, bisection width and wiring complexity. The results show that the MGN design has better performance than other network topologies such as hierarchical Gaussian network (HGN).